The clinical and hemodynamic effects of propranolol, pindolol and verapamil in the treatment of exertional angina pectoris. - Johnston, D L (1984)
The efficacy of two beta-receptor antagonists, propranolol and pindolol, was compared with that of a calcium antagonist, verapamil, in the treatment of exertional angina pectoris in 22 men (mean age 51 years). The clinical response and left ventricular function were evaluated with treadmill exercise and with radionuclide ventriculography performed while the patient was at rest or exercising supine with a bicycle ergometer. All the treatments significantly prolonged exercise duration (p less than 0.001) and reduced the number of patients terminating treadmill exercise because of angina (p less than 0.05). The resting heart rate was decreased markedly (p less than 0.001) by propranolol but only slightly (p less than 0.05) by pindolol and verapamil. The left ventricular ejection fraction during rest was unchanged by any treatment, but that during exercise was improved (p less than 0.05) by all the treatments. Patients who failed to gain relief from angina with one of the drugs often responded to another, and adverse reactions occurring with one drug did not necessarily occur with another. In summary, pindolol and verapamil were safe and effective alternatives to propranolol in the treatment of the exertional angina pectoris of these patients.